Analisis Kontribusi Sektor Pariwisata Terhadap Perekonomian Provinsi Jawa Barat (Analisis Lq Dan Shift Share) - Wulandari, Wisi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2018)
The purpose of this study is to determine capability of tourism sector become economic basis for West Java Province. In addition to know the contribution of the tourism sector to the economic development of West Java Province in this case is related with GDP and the range of data period 2004-2015. Based on the LQ analysis (LQ>1) tourism sector become an economic basis in West Java. While the SSA results mention that the tourism sector gives a real impact on the economic of West Java development. Accordingly, the Provincial government of West Java as a policy maker should be able to be directed to the economic sectors basis for decision making in West Java development.